2014
DOI: 10.1172/jci73639
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 identifies the patient-specific CD8+ tumor-reactive repertoire infiltrating human tumors

Abstract: Adoptive transfer of tumor-infiltrating lymphocytes (TILs) can mediate regression of metastatic melanoma; however, TILs are a heterogeneous population, and there are no effective markers to specifically identify and select the repertoire of tumor-reactive and mutation-specific CD8 + lymphocytes. The lack of biomarkers limits the ability to study these cells and develop strategies to enhance clinical efficacy and extend this therapy to other malignancies. Here, we evaluated unique phenotypic traits of CD8 + TIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

78
816
5
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 927 publications
(902 citation statements)
references
References 71 publications
78
816
5
3
Order By: Relevance
“…While HPV − HNC patients showed no detectable staining for HPV-specific multimers (not shown), a subset of HPV-16 HLA-A2:E7(11–20)-specific T cells detected in the circulation of HPV + patients were found to express PD-1 (8.5%, Figure 1(c)) as a marker of antigen experience and exhaustion. As PD-1 + T cells appear to be clonal expansions of anti-tumor effector cells in the tumor microenvironment, 7 the relationship between TCR and anti-tumor efficacy was further investigated, using a broader method than multi-color flow cytometry.
10.1080/2162402X.2018.1494112-F0001Figure 1. Antigen specific T cells of HNC patients express exhaustion markers . Antigen specific CD8 + T cells were identified using EGFR (853–861) -, MAGE (271–279) - and HPV-E7 (11–20) -specific tetramers/ pentamers and counter-stained with PD-1 and CTLA-4 (t test, HPV + n = 18, HPV − n = 18).
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While HPV − HNC patients showed no detectable staining for HPV-specific multimers (not shown), a subset of HPV-16 HLA-A2:E7(11–20)-specific T cells detected in the circulation of HPV + patients were found to express PD-1 (8.5%, Figure 1(c)) as a marker of antigen experience and exhaustion. As PD-1 + T cells appear to be clonal expansions of anti-tumor effector cells in the tumor microenvironment, 7 the relationship between TCR and anti-tumor efficacy was further investigated, using a broader method than multi-color flow cytometry.
10.1080/2162402X.2018.1494112-F0001Figure 1. Antigen specific T cells of HNC patients express exhaustion markers . Antigen specific CD8 + T cells were identified using EGFR (853–861) -, MAGE (271–279) - and HPV-E7 (11–20) -specific tetramers/ pentamers and counter-stained with PD-1 and CTLA-4 (t test, HPV + n = 18, HPV − n = 18).
…”
Section: Resultsmentioning
confidence: 99%
“…In the tumor microenvironment, T cells expressing PD-1 have been identified as clonal expansion of tumor reactive T cell populations, thus representing functionally important components in order to eliminate tumor cells. 7 Furthermore, Gros and colleagues were able to recently identify PD1 + CD8 + T cells in circulation of three melanoma patients that targeted unique patient-specific neoantigens. 31 Our findings, that tumor antigen specific T-cells (including EGFR, MAGE and HPV) in the periphery express PD-1 and CTLA-4, support these observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAG3 expression is upregulated on T cells after activation and differentiation, 54 , 55 and intra-tumoral T cells that recognize tumor antigens are characterized by expression of LAG3 and other inhibitory receptors. 56 Although chronic tumor antigen stimulation in the tumor microenvironment can induce T cell exhaustion with simultaneous induction of high expression of multiple inhibitory receptors, this does not mean that all CD8 + TIL which express one or more inhibitory receptors at any level are functionally exhausted. Indeed, a recent mouse study showed that tumor antigen-specific TIL which expressed LAG3 or PD-1 produced IFN-γ in situ and had cytolytic potential.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, besides its inhibitory effect on T-cell function, mainly exerted by dephosphorylating CD28, 14 PD-1 has recently been shown to be highly expressed in the effector phase of T cells, particularly in melanoma-reactive and clonally expanded CD8 + T-cells. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%